Relationship between CaSRs and LPS-injured cardiomyocytes - Han, Gang (Int J Clin Exp Pathol, 2018)
Objective: Calcium-sensing receptors (CaSRs) regulate systemic calcium homeostasis. Intracellular calcium concentration changes are initiating factors of endoplasmic reticulum stress and cell autophagy. Recent research has revealed that CaSRs play an important role in myocardial ischemia/reperfusion injury and other cardiovascular diseases. However, it remains unclear whether CaSRs are involved in lipopolysaccharide (LPS)-induced cardiomyocyte injury. Methods: Cultured neonatal rat cardiomyocytes were treated with LPS, with or without pretreatment by a CaSR specific agonist SC-211006 or CaSR specific antagonist SC-207394. The ultrastructure of cardiomyocytes was observed using a transmission electron microscope, and the expression of CaSR, GRP78, LC3B, CytC and Bcl-2 proteins were detected by western blot. Results: Compared with the control group, LPS increased cardiomyocyte injury and the expression of CaSR, GRP78, LC3B and CytC proteins, but decreased the expression of Bcl-2. Compared with the LPS group, pretreatment with SC-211006 further enhanced cardiomyocyte damage and the expression of CaSR, GRP78, LC3B and CytC, but reduced the expression of Bcl-2. Conversely, pretreatment with SC-207394 decreased cardiomyocyte injury and the protein expression of CaSR, GRP78, LC3B and CytC, but increased the expression of Bcl-2. Conclusion: Our results suggest that CaSRs are involved in LPS-induced rat cardiomyocyte injury via the activation of endoplasmic reticulum stress and autophagy.